Assessment of earthworm diversity and pesticide toxicity in Eudrilus Eugeniae - Jeyaprakasam, Archana; Muniyandi, Biruntha; James, Arockia John Paul; Karmegam, Natchimuthu; Ponnuchamy, Kumar (Environmental chemistry and ecotoxicology, 2021)
Pesticides have become an inseparable part of modern agricultural production and technology. Malathion pesticide more than 139,000 MT production capacity annually, with more than 219 technical grade and manufacturing units, and over 4000 formulation units in India. The earthworm survey was carried out in all the five sites at regular monthly intervals. In this present work, a total of six earthworms from five different species were collected from different vegetation such as garden, pond, paddy, edible tubers, and sugarcane field. The organophosphate pesticide malathion is selected as a target compound for toxicity study. The earthworm species Eudrilus eugeniae was used as a model organism. Contact toxicity was studied by filter paper method and to observe the mortality rate of different concentrations of pesticide for 24 and 48 h. The soil toxicity study was done by using artificial soil for 14 days. Surviving worms also had reduced body weight, and in some cases, morphological changes. Enzymatic activities of SOD, CAT, and protease were evaluated in the vermicast of pesticide-treated earthworm. This study refers to the earthworm population between pesticide-contaminated and unpolluted soil. This work will provide information to estimate the toxic level of Malathion against the earthworm. •Total of six earthworms from five different species was collected from different vegetation•Organophosphate pesticide malathion is selected as a target compound for toxicity study•Surviving worms also had reduced body weight and in some cases,